Prospective Study of Malabsorption and Malnutrition After Esophageal and Gastric Cancer Surgery. Issue 5 (November 2015) - Heneghan, Helen M.; Zaborowski, Alexandra; Fanning, Michelle; McHugh, Aisling; Doyle, Suzanne; Moore, Jenny; Ravi, Nayarasamy; Reynolds, John V.
Abstract : Objective: To study malabsorption and malnutrition after curative resection of esophageal and gastric cancer. Design: Prospective cohort study. Background: Improved cure rates for esophageal and gastric cancer have increased focus on health-related quality of life (HR-QL) in survivorship. Although malnutrition is well described in long-term follow-up, and gastrointestinal symptoms are common, data on gut and pancreatic-related malabsorption are scant. Methods: Disease-free patients at least 18 months after esophageal or gastric oncologic resections represented the study cohort. A modified Gastrointestinal Symptom Rating Scale questionnaire was completed, and weight, fecal elastase (FE), albumin, vitamins, and micronutrients measured preoperatively and at 1, 6, and 18 to 24 months postoperatively. Small intestinal bacterial overgrowth (SIBO) and changes in body composition were also evaluated postoperatively. Results: At a median follow-up of 23 months, 45 of 66 patients in a consecutive series were disease-free. Mean weight (78 ± 19 vs 67 ± 16 kg), body mass index (27 ± 5 vs 24 ± 5 kg/m 2 ), Vitamin A (1.7 ± 0.6 vs 1.2 ± 0.4 umol/L), and Vitamin E (28 ± 7 vs 20 ± 7 umol/L) were significantly decreased ( P  < 0.01) at last follow-up compared with preoperatively. Malabsorption was evident in 73% of patients, of whom 44% had FE < 200 μg/g and 38% had evidence of SIBO. Total body fat-free mass (175 ± 96 vs 84 ± 71, P  < 0.001) and skeletal muscle index (44 ± 8 vs 39 ± 8, P  = 0.007) were significantly decreased at 18 to 24 months. Conclusions: Malabsorption and malnutrition are prevalent in survivorship of esophageal and stomach cancer. This may be underappreciated, and both gut and pancreatic insufficiency represent modifiable targets in the interdisciplinary approach to recovery of HR-QL. Abstract : Supplemental Digital Content is available in the text